2023
DOI: 10.1101/2023.11.29.23298779
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Supraspinal control of motoneurons after paralysis enabled by spinal cord stimulation

Josep-Maria Balaguer,
Genis Prat-Ortega,
Nikhil Verma
et al.

Abstract: Spinal cord stimulation (SCS) restores motor control after spinal cord injury (SCI) and stroke. This evidence led to the hypothesis that SCS facilitates residual supraspinal inputs to spinal motoneurons. Instead, here we show that SCS does not facilitate residual supraspinal inputs but directly triggers motoneurons action potentials. However, supraspinal inputs can shape SCS-mediated activity, mimicking volitional control of motoneuron firing. Specifically, by combining simulations, intraspinal electrophysiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…One case–control study showed that a single session of AC-TSCS, with and without carrier frequency, had an excitatory effect at the spinal level as measured by CMEPs in both individuals living with chronic incomplete SCI and healthy controls ( Benavides et al, 2020 ). Indeed, a recent study that combined biophysical modeling with animal and human (individuals with SCI and stroke) electrophysiological experiments indicated that in the presence of supraspinal inputs, subthreshold excitatory postsynaptic potentials induced by spinal stimulation can be transformed into action potentials that increase motor output ( Balaguer et al, 2023 ). Although a more detailed understanding of the neural mechanisms associated with spinal stimulation comes from preclinical and neurophysiological studies with epidural spinal cord stimulation, we believe that TSCS can also re-activate functionally silent pathways by enhancing the general level of excitability and bringing interneurons and motor neurons closer to the threshold of firing, thereby making the spinal circuits more likely to respond to both descending drives and ascending sensory information ( Taylor et al, 2021 ; Barss et al, 2022 ; Lin et al, 2022 ; Sayenko et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One case–control study showed that a single session of AC-TSCS, with and without carrier frequency, had an excitatory effect at the spinal level as measured by CMEPs in both individuals living with chronic incomplete SCI and healthy controls ( Benavides et al, 2020 ). Indeed, a recent study that combined biophysical modeling with animal and human (individuals with SCI and stroke) electrophysiological experiments indicated that in the presence of supraspinal inputs, subthreshold excitatory postsynaptic potentials induced by spinal stimulation can be transformed into action potentials that increase motor output ( Balaguer et al, 2023 ). Although a more detailed understanding of the neural mechanisms associated with spinal stimulation comes from preclinical and neurophysiological studies with epidural spinal cord stimulation, we believe that TSCS can also re-activate functionally silent pathways by enhancing the general level of excitability and bringing interneurons and motor neurons closer to the threshold of firing, thereby making the spinal circuits more likely to respond to both descending drives and ascending sensory information ( Taylor et al, 2021 ; Barss et al, 2022 ; Lin et al, 2022 ; Sayenko et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…We believe that further understanding of the corticospinal mechanisms associated with recovery of upper limb motor function following TSCS intervention specifically targeted at the cervical enlargement is of significant importance after SCI as cervical spinal motorneurons receive extensive inputs from corticospinal tracts ( Balbinot et al, 2023 ). Emerging evidence also suggests that the neuroplasticity induced by spinal cord stimulation also depends on the number of residual supraspinal inputs survived, thereby limiting the effects of TSCS in situations involving a substantial loss of supraspinal axons ( Balaguer et al, 2023 ). Future studies should subgroup participants based on the location and severity of the lesion to further investigate whether neuroplasticity-induced changes following TSCS vary among different subgroups with SCI.…”
Section: Discussionmentioning
confidence: 99%